Cover Feature: Formation of Highly Ordered Molecular Porous 2D Networks from Cyano‐Functionalized Porphyrins on Cu(111) (Chem. Eur. J. 59/2020). Issue 59 (6th October 2020) - Adhikari, Rajan; Siglreithmaier, Gretel; Gurrath, Martin; Meusel, Manuel; Kuliga, Jan; Lepper, Michael; Hölzel, Helen; Jux, Norbert; Meyer, Bernd; Steinrück, Hans‐Peter; Marbach, Hubertus
Abstract : Cyano‐functionalized tetraphenyl porphyrins fused together by cyano‐Cu‐cyano interactions with Cu adatoms form a snowflake‐like structure with a triangular central pore on Cu(111). More information can be found in the Full Paper by B. Meyer, H.‐P. Steinrück, et al. on page 13408 .